Functional analysis of TLK2 variants and their proximal interactomes implicates impaired kinase activity and chromatin maintenance defects in their pathogenesis. Issue 2 (15th December 2020) - Pavinato, Lisa; Villamor-Payà, Marina; Sanchiz-Calvo, Maria; Andreoli, Cristina; Gay, Marina; Vilaseca, Marta; Arauz-Garofalo, Gianluca; Ciolfi, Andrea; Bruselles, Alessandro; Pippucci, Tommaso; Prota, Valentina; Carli, Diana; et al.
Abstract : Introduction: The Tousled-like kinases 1 and 2 (TLK1 and TLK2) are involved in many fundamental processes, including DNA replication, cell cycle checkpoint recovery and chromatin remodelling. Mutations in TLK2 were recently associated with 'Mental Retardation Autosomal Dominant 57' (MRD57, MIM# 618050), a neurodevelopmental disorder characterised by a highly variable phenotype, including mild-to-moderate intellectual disability, behavioural abnormalities, facial dysmorphisms, microcephaly, epilepsy and skeletal anomalies. Methods: We re-evaluate whole exome sequencing and array-CGH data from a large cohort of patients affected by neurodevelopmental disorders. Using spatial proteomics (BioID) and single-cell gel electrophoresis, we investigated the proximity interaction landscape of TLK2 and analysed the effects of p.(Asp551Gly) and a previously reported missense variant (c.1850C>T; p.(Ser617Leu)) on TLK2 interactions, localisation and activity. Results: We identified three new unrelated MRD57 families. Two were sporadic and caused by a missense change (c.1652A>G; p.(Asp551Gly)) or a 39 kb deletion encompassing TLK2, and one was familial with three affected siblings who inherited a nonsense change from an affected mother (c.1423G>T; p.(Glu475Ter)). The clinical phenotypes were consistent with those of previously reported cases. The tested mutations strongly impaired TLK2 kinase activity. Proximal interactions between TLK2 and other factors implicated in neurological disorders, including CHD7, CHD8, BRD4 and NACC1, were identified. Finally, we demonstrated a more relaxed chromatin state in lymphoblastoid cells harbouring the p.(Asp551Gly) variant compared with control cells, conferring susceptibility to DNA damage. Conclusion: Our study identified novel TLK2 pathogenic variants, confirming and further expanding the MRD57-related phenotype. The molecular characterisation of missense variants increases our knowledge about TLK2 function and provides new insights into its role in neurodevelopmental disorders.